Probiotic characterization of Levilactobacillus brevis CM04 isolated from Hanoi-pickled Dong Du (Brassica campestris L. - Nguyen, Thi Huong; Dang, Bao Son; Do, Phuong Khanh; Ta, Thi Thu Thuy; Nguyen, Thanh Chung (Vietnam Journal of Biotechnology, 2025)
Hyperuricemia, characterized by increasing concentrations of serum uric acid, is associated with metabolic disorders such as gout, diabetes, and heart diseases. Hyperuricemia is a prevalent condition with a rapidly increasing global incidence. Probiotics represent the promising option for preventing and treating hyperuricemia without side effects. Microorganisms can be considered probiotics; they must pass safety evaluations. This study assessed the probiotic characteristics of Levilactobacillus brevis CM04. L. brevis CM04 was isolated from Hanoi-pickled Dong Du (Brassica campestris L.) and exhibited high purine degradation ability. This strain showed a strong survival capability in the oral-gastrointestinal assay and adhered to intestinal cells more effectively than Lactobacillus rhamnosus GG (LGG). CM04 grew well in both media with and without sodium taurocholate, however, it did not exhibit bile salt deconjugation activity. Additionally, CM04 exhibited strong antimicrobial activity against pathogenic bacteria and sensitivity to all tested antibiotics. These findings indicate that L. brevis CM04 possesses probiotic characteristics.